KONTEKS IBADAH MENURUT AL-QURAN - Abdul Kallang (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2018)
Worship to God in the broad sense, also has a wide scope. Some are directly or indirectly. Directly is by way of worship hablun minallah. Indirectly is by fostering hablun minannas according to the command of God. The doctrine of worship should not be superficially understood, in which some interpret the worship to be merely a mahdhah worship, or only concerning ritual aspects such as prayer, fasting, and hajj. In fact, worship in the broad sense must also be understood, namely everything that is pleasing and favored by God in the form of deeds and speech is included worship.KeywordsWorship; Al-Quran; hablun minallah; hablun minannas